The Based Instructional Materials Development Biology Environmental Issues in Improving Students’ Knowledge on The Basic Concepts Of Ecology - Lasmaria Nami Simanungkalit (Universitas Negeri Jakarta, 2017)
The environmental crisis that occurred in late sourced from the mistakes of human behavior to the views and error nature exploration. The efforts made by some countries to address the environmental issues have been integrated in education. But the school still experiencing problems on the biology subject-based environmental issues. It is therefore necessary materials specifically to increase students' knowledge about the basic concepts of ecology. A Research and Development of teaching materials is based on the Borg and Gall (1983), but refers to the design of Dick and Carey (2009), involving 33 students of class XI IPA SMAN 86 Bintaro, South- Jakarta, as an experimental class and class XI IPA, SMAN 39 Cijantung East-Jakarta, as the control class. There are two biological development of teaching materials developed. There are five t-tests to verify the biological development of teaching materials based on environmental issues. Research results indicated that there is a significant difference between mean of gain score obtained from post-test and pre-test at experiment group compared to control group. Then the development of teaching materials based biology to environmental issues can be disseminated to the students' knowledge of the basic concepts of ecology.